2014
DOI: 10.1097/shk.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Thrombolytics Reduce Lung Microclot and Leukocyte Infiltration After Acute Blood Loss

Abstract: We showed previously that a 30% blood loss in rats, without resuscitation, caused significant accumulation of microthrombi and leukocytes within the pulmonary circulation by 24 h. We hypothesized that the microthrombi formed spontaneously as a consequence of hemorrhage-induced stasis within the low-pressure pulmonary circuit and that the leukocytes were attracted to them. This suggested that elimination of the microthrombi, using an inhaled thrombolytic agent, could prevent the neutrophil sequestration after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As such, inhaled thrombolytic therapy has been of interest for prevention of ARDS and has been studied in rat models showing mitigation of microthrombus formation and subsequent leukocyte accumulation (Conhaim, Watson et al 2014). …”
Section: Inhaled Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…As such, inhaled thrombolytic therapy has been of interest for prevention of ARDS and has been studied in rat models showing mitigation of microthrombus formation and subsequent leukocyte accumulation (Conhaim, Watson et al 2014). …”
Section: Inhaled Deliverymentioning
confidence: 99%
“…In a murine model of hemorrhagic shock, it has been shown that microthrombus formation precedes the subsequent accumulation of leukocytes and is likely due to sluggish blood flow in the low-pressure pulmonary circulation [Conhaim et al 2010]. As such, inhaled thrombolytic therapy has been of interest for prevention of ARDS and has been studied in rat models showing mitigation of microthrombus formation and subsequent leukocyte accumulation [Conhaim et al 2014].…”
Section: Inhaled Deliverymentioning
confidence: 99%